Incomplete Memories: The Natural Suppression of Tissue-Resident Memory CD8 T Cells in the Lung - Reagin, Katie L.; Klonowski, Kimberly D. (Frontiers in Immunology, 2018)
The yearly, cyclic impact of viruses like influenza on human health and the economy is due to the high rates of mutation of traditional antibody targets, which negate any pre-existing humoral immunity. However, the seasonality of influenza infections can equally be attributed to an absent or defective memory CD8 T cell response since the epitopes recognized by these cells are derived from essential virus proteins that mutate infrequently. Experiments in mouse models show that protection from heterologous influenza infection is temporally limited, and conferred by a population of tissue-resident memory (TRM) cells residing in the lung and lung airways. TRM are elicited by a diverse set of pathogens penetrating mucosal barriers and broadly identified by extravascular staining and expression of the activation and adhesion molecules CD69 and CD103. Interestingly, lung TRM fail to express these molecules, which could limit tissue retention, resulting in airway expulsion or death with concomitant loss of heterologous protection. Here, we make the case that respiratory infections uniquely evoke a form of natural immunosuppression whereby specific cytokines and cell-cell interactions negatively impact memory cell programming and differentiation. Respiratory memory is not only short-lived, but most of the memory cells in the lung parenchyma may not be bona-fide TRM. Given the quantity of microbes humans inhale over a lifetime, limiting cellular residence could be a mechanism employed by the respiratory tract to preserve organismal vitality. Therefore, successful efforts to improve respiratory immunity must carefully and selectively breach these inherent tissue barriers.